Perkembangan Lahan Terbangun Kota Pekanbaru Tahun 2000-2020 - Almegi, Almegi; Fatmawati, Fatmawati (Universitas Negeri Yogyakarta, 2023)
This research aims describe the development of built-up area and identify trends the development of built-up area in Pekanbaru City in 2000-2020. The approach in research is descriptive quantitative with stages of temporal landsat image interpretation, field verification, and spatial analysis. The study population is the entire pixel data in satellite imagery with sampling techniques for the image interpretation process. Supervised classification is used in the interpretation process, kappa index with 22 sample points is used to test the accuracy of the interpretation results, and map overlays are used in spatial analysis. The results of the analysis show that in the last two decades (2000-2020) the built-up area in Pekanbaru City increased by 13,45% (85,99 km2) with an average increase of 0.67% (4,30 km2) annually. Spatially, the distribution of development of built up area is unevenly, but forms a patterns and directions that tends to be the same, namely the pattern of spreading from the city center to the fringe area with development trends in the south and southwest following the main road route.